2013
DOI: 10.1371/journal.pone.0082018
|View full text |Cite
|
Sign up to set email alerts
|

Added Value of HER-2 Amplification Testing by Multiplex Ligation-Dependent Probe Amplification in Invasive Breast Cancer

Abstract: BackgroundHER-2 is a prognostic and predictive marker, but as yet no technique is perfectly able to identify patients likely to benefit from HER-2 targeted therapies. We aimed to prospectively assess the added value of first-line co-testing by IHC, and multiplex ligation-dependent probe amplification (MLPA) and chromogenic in situ hybridization (CISH).MethodsAs local validation, HER-2 MLPA and CISH were compared in 99 breast cancers. Next, we reviewed 937 invasive breast cancers, from 4 Dutch pathology laborat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 37 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…It is of paramount clinical importance to carefully define the HER2 status in these uncommon subsets of BC in which the mean CEP17 copy number drives in the final classification based on the ISH algorithm proposed by the guidelines. To this end, we evaluated whether MLPA, a quantitative molecular method [ 26 , 28 , 29 , 40 ] may be a helpful reflex test to define the HER2 status in 54 BC presenting a non classical HER2 ISH results (4.0–5.9 HER2 gene s/n). One hundred and sixteen BC including 55 HER2 clearly amplified (>6.0 gene s/n) and 61 clearly non amplified (less than 4.0 gene s/n, ratio < 2.0) BC represented our control series.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is of paramount clinical importance to carefully define the HER2 status in these uncommon subsets of BC in which the mean CEP17 copy number drives in the final classification based on the ISH algorithm proposed by the guidelines. To this end, we evaluated whether MLPA, a quantitative molecular method [ 26 , 28 , 29 , 40 ] may be a helpful reflex test to define the HER2 status in 54 BC presenting a non classical HER2 ISH results (4.0–5.9 HER2 gene s/n). One hundred and sixteen BC including 55 HER2 clearly amplified (>6.0 gene s/n) and 61 clearly non amplified (less than 4.0 gene s/n, ratio < 2.0) BC represented our control series.…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies which compared MLPA and ISH techniques, were broadly concordant with our results. The data reported so far have demonstrated that there are specific scenarios in which MLPA may be of particular value in HER2 testing when selecting patients to undergo anti HER2 treatment [ 26 28 , 40 ]. In this context, BC patients displaying a mean of the HER2 gene s/n ranging between 4.0–5.9, including both low amplified and equivocal tumors, could benefit most from MLPA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Third, they can be multiplexed, allowing simultaneous interrogation of multiple genes or different parts of genes, representing an ideal and low cost prescreening tool. Head-to-head comparisons between IHC, FISH, and CISH have shown good correlation among technologies [ 106 - 109 ]. The main weaknesses of PCR-based assays are that they do not preserve tissue morphology, may require sample macro- or microdissection to enrich for tumor content, heterogeneity can be missed and contamination with normal or ductal carcinoma in situ may lead to both false-negative and false-positive results.…”
Section: Methodologiesmentioning
confidence: 99%